Utilization of Blood Flow Restriction Therapy with a Former Triathlete After Total Knee Arthroplasty: A Case Report - Christopher Keating; Stephanie Muth; Cameron Hui; Lisa T Hoglund (International Journal of Sports Physical Therapy)
# Introduction and Purpose